Groans of the Groin Flap - J. C. Sharma; D. V. Chhibber; A. S. Bath (Indian Journal of Plastic Surgery)
The groin flap in India does not behave as well as it does in the temperate climate. Therefore all is not well, when a groin flap is used. The problems observed by us in our five year study of sixty groin flaps have been highlighted through this paper.